2018
DOI: 10.1002/adma.201706423
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Dependent Charge Transfer Rate in Oligopeptides

Abstract: It is shown that "spontaneous magnetization" occurs when chiral oligopeptides are attached to ferrocene and are self-assembled on a gold substrate. As a result, the electron transfer, measured by electrochemistry, shows asymmetry in the reduction and oxidation rate constants; this asymmetry is reversed between the two enantiomers. The results can be explained by the chiral induced spin selectivity of the electron transfer. The measured magnetization shows high anisotropy and the "easy axis" of magnetization is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 34 publications
6
54
1
Order By: Relevance
“…One plausible explanation comes from the chiral‐induced spin selectivity (CISS) effect, i.e., the filtering of electrons depending on their spin by chiral molecules . CISS has been observed for a variety of systems: poly(thiophene) with chiral side‐chains, cysteine, oligopeptides, protein, carbon nanotubes functionalized with single‐stranded DNA, chiral self‐assembled monolayer, and even helicenes . CISS can be intuitively understood.…”
Section: Charge Transportmentioning
confidence: 99%
“…One plausible explanation comes from the chiral‐induced spin selectivity (CISS) effect, i.e., the filtering of electrons depending on their spin by chiral molecules . CISS has been observed for a variety of systems: poly(thiophene) with chiral side‐chains, cysteine, oligopeptides, protein, carbon nanotubes functionalized with single‐stranded DNA, chiral self‐assembled monolayer, and even helicenes . CISS can be intuitively understood.…”
Section: Charge Transportmentioning
confidence: 99%
“…However,the mean molecular area occupied by the T-ZnTPP layer in the two films is different, being 240 2 for film 1 and 476 2 for film 2.T his difference suggests that the porphyrin molecular orientation on the gold surface in the two films is different (the size of the molecule is 480 2 in ap lanar arrangement and 200 2 in av ertical arrangement). [36] However,e ven when the dipole moment and spin effect do not favor ET,t his kind of molecular spacers can better mediate the ET process than other molecules (such as alkanethiols). It has already been demonstrated that porphyrin aggregation and molecular orientation influence photocurrent efficiency.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[11c, 34] Moreover,t he peptide length of Tr (Lys) (estimated to be about 17 ) [35] suggests the onset of at unnelling mechanism for film 2, [11b] favouring direct ET from the Au electrode to ZnTPP.T r(Lys) is thus likely to have ap romoting effect on the ET rate.I th as been demonstrated that the intramolecular hydrogen bonds actively promote ET, and that helical peptides behave like molecular photodiodes, due to the dipole moment [14a] and spin-dependent effects along the helical axis. [36] However,e ven when the dipole moment and spin effect do not favor ET,t his kind of molecular spacers can better mediate the ET process than other molecules (such as alkanethiols).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However, the recent finding of spin-selective electron transport through chiral molecules by Naaman et al, i.e., the so-called chirality-induced spin selectivity (CISS) effect, suggests an alternative method of using organic materials as spin filters for spintronics applications 1417 . Although its microscopic mechanism is still under debate, the CISS effect has been validated by numerous experiments such as photoelectron spectroscopy 14,18 , magnetoresistance (MR) measurements, photoinduced electron transfer measurements 1921 , spin-polarized conductive atomic force microscopy (AFM) 2224 , single-molecule scanning tunnel microscopy 25 , and X-ray circular dichromism measurements 26 . Moreover, the CISS effect was already demonstrated in several applications such as magnetic memory devices 2729 , spin-injection devices 30 , water splitting 31,32 , and enantiomer separation 33,34 .…”
Section: Introductionmentioning
confidence: 99%